Parent preference in Switzerland for easy-to-use attributes of growth hormone injection devices quantified by willingness to pay. (January 2014) - Meinhardt, Udo; Eiholzer, Urs; Seitz, Lisa; Bøgelund, Mette; Kappelgaard, Anne-Marie
Abstract : Sustained treatment adherence, usually over long periods of time, is critical to the success of growth hormone (GH) therapy. However, adherence rates are often poor which may result in suboptimal clinical outcomes. The type of device used by patients to administer their GH can influence adherence. Offering patients a choice of device maximizes the chance of adherence to treatment. Multiple factors will influence a patient's choice of device, depending on individual priorities. This study evaluated the most preferred features of GH injection devices by parents using a web-based questionnaire and as assessed by their willingness to pay for specific device features. The results show that parents are willing to pay for device features facilitating ease of use.